Pola Perilaku Masyarakat Pengguna Transportasi Umum pada Masa Pandemi di Kecamatan Karawaci Kota Tangerang - Saputri, Bella Hanny; Haryono, Haryono (ARZUSIN, 2022)
Public transportation is one of the supporting activities of the community in every area of their life. Then, the implementation of public transportation activities dos not only pay attention to the transportation system, but is supported by the behavior of its users. From the service of transportation modes, it is maximal enough for some community groups, although development is still needed but does not become an obstacle in the transportation process.However, in transportation activities, people’s behavior is still found that deviates from the applicable standards. The study aims to: (1) find out the behavior patterns of people who use public transportation in the Karawci Sub-distict, Tangerang City during the Covid-19 pandemic, and (2) find out the comparison of behavior patterns of people who use public transportation before and after Covid-19 pandemic. The study uses descriptive qualitative methods and data collection techniques through observation, interviews, and documentation. The results of this study indicate that there are changes in people behavior patterns in using public transportation during the Covid-19 pandemic in carrying out transportation activities.